2019
DOI: 10.1002/oby.22409
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Maternal Weight Status Before, During, and After Pregnancy with Breast Milk Hormone Concentrations

Abstract: Objective The aim of this study was to test associations of prepregnancy BMI, gestational weight gain, oral glucose challenge test results, and postpartum weight loss as predictors of breast milk leptin, insulin, and adiponectin concentrations and whether these relationships vary over time. Methods Milk was collected at 1 and 3 months from 135 exclusively breastfeeding women from the longitudinal Mothers and Infants Linked for Healthy Growth (MILk) study. Hormones were assayed in skimmed samples using ELISA. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 40 publications
(68 reference statements)
6
45
1
Order By: Relevance
“…As we postulated in a previous publication in the same cohort [19], maternal obesity may persist after pregnancy, and alter breast milk characteristics [8,9,19,34]: this includes neuroactive components for infant cognitive development [9,34]. However, we found that maternal obesity before pregnancy was a separate influence, unrelated to breast milk factors.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…As we postulated in a previous publication in the same cohort [19], maternal obesity may persist after pregnancy, and alter breast milk characteristics [8,9,19,34]: this includes neuroactive components for infant cognitive development [9,34]. However, we found that maternal obesity before pregnancy was a separate influence, unrelated to breast milk factors.…”
Section: Discussionsupporting
confidence: 57%
“…First, maternal characteristics contribute to breast milk characteristics: mothers who are obese may have more difficulty with breast milk expression to meet the demands of the infant [8]. Moreover, maternal obesity alters breast milk composition: this includes neuroactive components, e.g., leptin and adiponectin [9]. Exposure to these compounds has been shown to influence infant cognitive performance [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we aim to determine the microbiota composition of mothers and children (faecal, oral, vaginal, breast milk) and determine the role of weight loss herein. In addition, breast milk composition/metabolome will be investigated,76 77 and placenta tissue will be collected for RNA-sequencing analysis, histology and epigenetics.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Presently, the majority of human milk studies do use BMI as a measure of maternal adiposity, often without discussion of its limitations (Andreas et al, 2014; Chan et al, 2018; Dietz & Bellizzi, 1999; Kugananthan et al, 2017; Martin et al, 2006; Prentice et al, 1994; Sadr Dadres et al, 2019). The fact that human milk leptin shows a consistent, positive association with maternal BMI (Table 3) at the time of milk collection illustrates the strength of the relationship between maternal adiposity and breast milk leptin, as such relationship is present even with such a poor measure of maternal adiposity (Fields et al, 2017; Houseknecht et al, 1997).…”
Section: Aim #3: Review the Evidence Showing How Using Maternal Bmi Amentioning
confidence: 99%